The Evolution of Temporal and Spatial Patterns of Carbon Monoxide Concentrations in the Metropolitan Area of Sao Paulo, Brazil - Flavia Noronha Dutra Ribeiro; Delhi Teresa Paiva Salinas; Jacyra Soares; Amauri Pereira de Oliveira; Regina Maura de Miranda; Luana Antunes Tolentino Souza (Advances in Meteorology)
The Environmental Agency of Sao Paulo has a large dataset of carbon monoxide measurements: 20 years of records in 18 automatic stations inside the metropolitan area. However, a thorough investigation on the time evolution of CO concentration tendency and cycles also considering spatial variability is lacking. The investigation consists of a trend line analysis, a periodogram analysis, a correlation between CO concentration and meteorological variables, and spatial distribution of CO concentration. Local and federal policies helped in decreasing CO concentrations and the highest decreasing rate was 0.7% per month. This tendency is lately stabilizing, since the vehicles fleet is increasing. CO most relevant cycles are annual and diurnal and a few series indicate a weekly cycle. Diurnal cycle shows two peaks, morning and evening rush hours, 1.2 and 1.1 ppm, respectively, in 2012. However, lately there is an extended evening peak (20 h to 23 h), related to changes in emission patterns. The spatial analysis showed that CO concentration has high spatial variability and is influenced by proximity to heavy traffic and vegetated areas. The present work indicates that several processes affect CO concentration and these results form a valuable basis for other studies involving air quality modeling, mitigation, and urban planning.